1998
DOI: 10.1086/311234
|View full text |Cite
|
Sign up to set email alerts
|

1E 0657−56: A Contender for the Hottest Known Cluster of Galaxies

Abstract: We identify the extended Einstein IPC X-ray source, 1E0657-56, with a previously unknown cluster of galaxies at a redshift of z = 0.296. Optical CCD images show the presence of a gravitational arc in this cluster and galaxy spectra yield a cluster velocity dispersion of 1213 +352 −191 km s −1 . X-ray data obtained with the ROSAT HRI and ASCA indicate that 1E0657-56 is a highly luminous cluster in which a merger of subclusters may be occurring. The temperature of the hot gas in 1E0657-56 is kT = 17.4 ± 2.5keV, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 25 publications
1
100
0
3
Order By: Relevance
“…The early evidence for intracluster light (Welch & Sastry 1971;Mattila 1977) has recently been confirmed with the detection of additional low surface brightness structures interpreted as tidal debris from recent galaxy interactions (Gregg & West 1998;Trentham & Mobasher 1998). With an X-ray temperature of ≈8 keV, Abell 1656 is the hottest of the observed clusters, and in fact lies near the upper end of the X-ray luminosity -temperature correlation (Tucker et al 1998).…”
Section: Abell 1656 (Coma)mentioning
confidence: 83%
“…The early evidence for intracluster light (Welch & Sastry 1971;Mattila 1977) has recently been confirmed with the detection of additional low surface brightness structures interpreted as tidal debris from recent galaxy interactions (Gregg & West 1998;Trentham & Mobasher 1998). With an X-ray temperature of ≈8 keV, Abell 1656 is the hottest of the observed clusters, and in fact lies near the upper end of the X-ray luminosity -temperature correlation (Tucker et al 1998).…”
Section: Abell 1656 (Coma)mentioning
confidence: 83%
“…Dark matter is now an observational fact. We see the effects of dark matter from rotation curves [356], gravitational lensing [357], the Bullet cluster [358,359], and even in the cosmic microwave background [10]. In fact, the CMB shows that nearly 85% of the matter in the Universe is dark matter [10].…”
Section: New Particles and Structure Formationmentioning
confidence: 99%
“…Here we report on five high-redshift, gravitationally lensed objects we have found in the background of the cluster 1E0657-56. Tucker et al (1998) identified the extended Einstein source 1E0657-56 with a cluster of galaxies at a redshift of z = 0.296 showing a velocity dispersion, measured from 13 galaxies, of σ gal ≈ 1200 km s −1 . X-ray data from ROSAT and ASCA indicate that merging of at least two subclusters occurs in this highly luminous X-ray cluster.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray data from ROSAT and ASCA indicate that merging of at least two subclusters occurs in this highly luminous X-ray cluster. Tucker et al (1998) derive a temperature of the hot gas in 1E0657-56 of kT ≈ 17 keV. Note, however, that Yaqoob (1998) reanalyzed the X-ray data and derived a temperature of kT ≈ 12 keV only.…”
Section: Introductionmentioning
confidence: 99%